2021
DOI: 10.1038/s41419-021-03755-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CEP70 function affects acrosome biogenesis and flagella formation during spermiogenesis

Abstract: The spermatogenesis process is complex and delicate, and any error in a step may cause spermatogenesis arrest and even male infertility. According to our previous transcriptomic data, CEP70 is highly expressed throughout various stages of human spermatogenesis, especially during the meiosis and deformation stages. CEP70 is present in sperm tails and that it exists in centrosomes as revealed by human centrosome proteomics. However, the specific mechanism of this protein in spermatogenesis is still unknown. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Previous data showed that CEP70 is involved in cilia formation and determines the length of the axoneme in zebrafish embryos ( 21 ). A recent study suggested that Cep70 −/− in mice caused male infertility, which resulted in abnormal acrosome structure and abnormal flagella ( 14 ). Furthermore, mice lacking CEP70 also exhibited disturbed spermiogenesis and increased germ-cell apoptosis, which led to a decrease in sperm count ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data showed that CEP70 is involved in cilia formation and determines the length of the axoneme in zebrafish embryos ( 21 ). A recent study suggested that Cep70 −/− in mice caused male infertility, which resulted in abnormal acrosome structure and abnormal flagella ( 14 ). Furthermore, mice lacking CEP70 also exhibited disturbed spermiogenesis and increased germ-cell apoptosis, which led to a decrease in sperm count ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…CEP70 was first found in proteomics studies of the centrosome and was suggested to express in the sperm tail ( 12 , 13 ). However, only one study has suggested that loss of CEP70 function is involved in male infertility ( 14 ). In that study, the authors found that CEP70 deficiency leads to male infertility in mice, which is associated with abnormalities in sperm flagellum, head and acrosome, and heterozygous mutations of CEP70 in four azoospermia patients were detected ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, acrosome development has a key role in this process. So far, more than 4000 genes have been reported to be involved in human spermatogenesis 4 . However, it is assumed that many genetic factors, which are yet to be discovered, can also affect spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10-15% of couples (50-80 million people) within the reproductive age are suffering from the condition of infertility, according to the recently revealed data by the World Health Organization (WHO). 1 Males are about 50% of the reported infertility cases. 2 Azoospermia can be described as the absence of sperms in two separately collected semen samples following centrifugation (1000×g for about 15 min).…”
Section: Introductionmentioning
confidence: 99%